Prevalence of Small Bowel Bacterial Overgrowth and Its Association with Nutrition Intake in Nonhospitalized Older Adults - Parlesak, Alexandr; Klein, Birgit; Schecher, Kerstin; Bode, J. Christian; Bode, Christiane (Journal of the American Geriatrics Society (JAGS), 2003)
OBJECTIVES: To determine the prevalence of small bowel bacterial overgrowth (SBBO) in older adults and to assess whether SBBO is associated with abdominal complaints and nutrient intake. DESIGN: Cross‐sectional survey. SETTING: Eight senior residence sites in Stuttgart, Germany. PARTICIPANTS: Older adults living independently in senior residence houses. MEASUREMENTS: The prevalence of SBBO was measured in 328 subjects, of whom 294 were aged 61 and older, by measuring hydrogen concentration (parts per million; ppm) in exhaled air after ingestion of 50 g glucose. Anthropometric data were obtained and nutritional status was recorded with a computer‐aided diet history. RESULTS: The prevalence of a positive hydrogen breath test (>10 ppm increase) was 15.6% in older adults, compared with 5.9% in subjects aged 24 to 59. The intake of inhibitors of gastric acid production contributed significantly to the high prevalence of a positive breath test in older adults, which was associated with lower body weight, lower body mass index, lower plasma albumin concentration, and higher prevalence of diarrhea. Subjects with a positive hydrogen breath test consumed significantly less fiber, folic acid, and vitamins B2 and B6 than those without. No difference was observed in the intake of energy, protein, fat, or carbohydrates. CONCLUSION: Prevalence of SBBO is associated with reduced body weight, which is paralleled by reduced intake of several micronutrients. Malabsorption resulting from diarrhea might be an aggravating factor contributing to weight loss in these subjects.